EFEKTIVITAS PEMANFAATAN ALOKASI DANA DESA (ADD) DI DESA RAMBAH JAYA KECAMATAN BANGUN PURBA KABUPATEN ROKAN HULU - ", Haryati; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Village Allocation Fund (ADD) is a part of the central and regional equalization funds devoted tothe village in implementing government services and community empowerment. But in reality theeffectiveness of the implementation and management is still not maximized. The existance of humanresources is inadequate, the construction of facilities and infrastructure are still yet to be realized, thegovernment needs to increase coordination between the government of village and the civil community. Theproblem in this research is how the effectiveness Rambah Jaya village government in achieving its goal inutilizing the Village Fund Allocation (ADD) and the factors that influence the effectiveness of.This study aims to determine the effectiveness of utilization of the Village Fund Allocation (ADD) Inthe village of Bangun Rambah Jaya District of Rokan Hulu and to find out the Village Fund AllocationUtilization Effectiveness (ADD) In the village of Bangun Rambah Jaya District of Rokan Hulu. The conceptof the theory that researchers use is organizational effectiveness by using Gibsons theory by looking at thegoals to be achieved Clarity, Clarity goal attainment strategy, process analysis and formulation of policysteady, careful planning, preparation of appropriate programs, availability of infrastructure andsurveillance systems and control didactic.The method used is qualitative research with descriptive data assessment. In collecting the data, theresearcher used interview techniques, observation and documentation specified by snowball samplingtechnique. The results showed that the utilization of the Village Fund Allocation (ADD) In the village ofBangun Rambah Jaya District of Rokan Hulu has not been effective because there are many village fundallocation unrealized. Also found are also government programs that have not been implemented village.The factors that influence the effectiveness of the utilization of the Village Fund Allocation (ADD) In thevillage of Bangun Rambah Jaya district of Rokan Hulu is a lack of human resources, poor coordination andlack of community participation in the implementation of.Keyword: Effectiveness, Utilization,Village Allocation Fund (ADD)